Membrane resistance and shunting inhibition: where biophysics meets state‐dependent human neurophysiology. (12th May 2016) - Paulus, Walter; Rothwell, John C.
Abstract : Electrical stimulation of a dendrite induces an EPSP that in the context of normal activation of the membrane can be recorded with a smaller amplitude at the soma (top). Additional activation of an inhibitory synapse on the way to the soma leads to shunting currents and prevents further transmission to the soma (bottom). Abstract: Activation of neurons not only changes their membrane potential and firing rate but as a secondary action reduces membrane resistance. This loss of resistance, or increase of conductance, may be of central importance in non‐invasive magnetic or electric stimulation of the human brain since electrical fields cause larger changes in transmembrane voltage in resting neurons with low membrane conductances than in active neurons with high conductance. This may explain why both the immediate effects and after‐effects of brain stimulation are smaller or even reversed during voluntary activity compared with rest. Membrane conductance is also increased during shunting inhibition, which accompanies the classic GABAA IPSP. This short‐circuits nearby EPSPs and is suggested here to contribute to the magnitude and time course of short‐interval intracortical inhibition and intracortical facilitation.